2011
DOI: 10.1007/s10753-011-9346-0
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide, a Sesquiterpene Lactone, Expresses Multiple Anti-cancer and Anti-inflammatory Activities

Abstract: Parthenolide, a naturally occurring sesquiterpene lactone derived from feverfew (Tanacetum parthenium), exhibits exceptional anti-cancer and anti-inflammatory properties, making it a prominent candidate for further studies and drug development. In this review, we briefly investigate molecular events and cell-specific activities of this chemical in relation to cytochrome c, nuclear factor kappa-light-chain enhancer of activated B cells (NF-κB), signal transduction and activation of transcription (STAT), reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(145 citation statements)
references
References 56 publications
4
141
0
Order By: Relevance
“…As a foundation for rational design of a multidrug regimen, we chose to evaluate parthenolide (PTL), a naturally occurring small molecule with reported anti-tumor properties in nearly all major forms of human cancer (20,21). Of particular interestis the activity of PTL as an agent in AML where it can target bulk tumor cells as well as the relatively rare AML stem cell population (22).…”
mentioning
confidence: 99%
“…As a foundation for rational design of a multidrug regimen, we chose to evaluate parthenolide (PTL), a naturally occurring small molecule with reported anti-tumor properties in nearly all major forms of human cancer (20,21). Of particular interestis the activity of PTL as an agent in AML where it can target bulk tumor cells as well as the relatively rare AML stem cell population (22).…”
mentioning
confidence: 99%
“…PTN, an inhibitor of NF-κB, could inhibit the systemic inflammation process. Earlier studies have confirmed that PTN could relieve the clinical and pathologic conditions associated with DN in db/db model, as well as decrease the inflammatory factors such as MCP-1 and IL-6 [18,19]. The findings of this study show that the inflammatory factors examined were extremely sensitive to PFA and PTN, as evidenced by the significant reduction of MCP-1 and IL-6 levels in THP-1, as well as the severe intracellular inactivation of p-STAT5 and NF-κB p65 pathways in DNU patients.…”
Section: Discussionmentioning
confidence: 86%
“…All the selected natural compound chemopreventive agents act as potent inhibitors of the NF-kB pathways. Wedelolactone, an inhibitor of IkB kinase, suppressed both TNFa-induced IkB phosphorylation and NF-kB phosphorylation at Ser 536 and Ser 468 (63), parthenolide (64)(65)(66), and honokiol (67,68). Costunolide inhibited the activation of Akt and NF-kB and the expression of antiapoptotic factors B-cell lymphoma-extra large (Bcl-xL) and X-linked inhibitor of apoptosis protein (XIAP) in 11Z cells (69)(70)(71), magnolol inhibits ERK1/2 phosphorylation and NF-kB translocation (72,73), PI3K/Akt/caspase and Fas-L/NF-kB signaling pathways might account for the responses of A375-S2 cell death induced by evodiamine (74,75).…”
Section: Nf-kb and Its Family Member Pathwaymentioning
confidence: 99%
“…Some selected agents are part, such as honokiol increases expression and activity of SPH-1 that further deactivates the STAT3 pathway (93), wedelolactone inhibits STAT1 dephosphorylation through specific inhibition of T-cell protein tyrosine phosphatase, which is important tyrosine phosphatase for STAT1 (94). Parthenolide shows strong STAT inhibition-mediated transcriptional suppression of proapoptotic genes (64)(65)(66), and alantolactone inhibits STAT3 activation in HepG2 cells (49). Therefore, these cumulative observations from both in vitro and/or in vivo studies have not only validated STAT as a novel target for cancer chemotherapy, and also hence provided the rationale for developing natural compound STAT inhibitors.…”
Section: Transducers and Activators Of Transcription And Its Family Mmentioning
confidence: 99%